2011
DOI: 10.1080/10934529.2011.532438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biomass open burning on particulate matter and polycyclic aromatic hydrocarbon concentration levels and PAH dry deposition in ambient air

Abstract: The objectives of the present study were to investigate particulate matter (PM) and polycyclic aromatic hydrocarbon (PAH) concentrations in ambient air during rice straw open burning and non-open burning periods. In the ambient air of a rice field, the mean PM concentration during and after an open burning event were 1828 and 102 μg m⁻³, respectively, which demonstrates that during a rice field open burning event, the PM concentration in the ambient air of rice field is over 17 times higher than that of the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Moreover, PAHs emitted from biomass burning can mix with other burning products, such as lignin-derived products (veratraldehyde and vanillic acid) and flavonoid compounds [ 46 ]. Photostable compounds (e.g., lignin-derived compounds) in the mixture can inhibit the photodegradation of PAHs and prolong their atmospheric life, enabling them to be transported [ 47 , 48 , 49 ]. In addition, the enhanced bioactivation of the PAH mixture can cause severe health hazards to humans [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PAHs emitted from biomass burning can mix with other burning products, such as lignin-derived products (veratraldehyde and vanillic acid) and flavonoid compounds [ 46 ]. Photostable compounds (e.g., lignin-derived compounds) in the mixture can inhibit the photodegradation of PAHs and prolong their atmospheric life, enabling them to be transported [ 47 , 48 , 49 ]. In addition, the enhanced bioactivation of the PAH mixture can cause severe health hazards to humans [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Italic and bold elements: errors not relevant to the "burned area" classification. Chiu et al (2011) indicated that RSOB is a significant PAH emission source because it substantially increases the particulate matter (PM), polycyclic aromatic hydrocarbon (PAH) concentration, and PAH dry deposition in the ambient air of a rice paddy during an open burning event. In this study, the annual emissions from RSOB were estimated to be 6,101 tons of PM (PM 10 + PM 2.5 ) and 2 tons of total PAH.…”
Section: Emissions Inventory For Rice Straw Open Burning In Taiwanmentioning
confidence: 99%
“…In addition, factor 3 in summer and factor 2 in autumn were heavily loaded with Acy and Fln. Previous studies have suggested that these 2 PAHs are related to biomass burning (Chiu et al ; Atzei et al ). In winter, factor 4 components explained 80% of the total variance, whereas factor 1 explained 38% of the variance, with heavy loadings of Phe, Chr, BaA, BbF, BaP, BkF, DbA, and BghiP.…”
Section: Resultsmentioning
confidence: 97%